Agmatine, a metabolite of arginine, improves learning and memory in streptozotocininduced Alzheimer's disease model in rats - (:unkn) unknown (My University, 2016)
0

Objective: Agmatine, the decarboxylation product of arginine produced by arginine decarboxylase, is a novel neurotransmitter and exists in the mammalian brain. Agmatine has been reported to modulate cognitive functions, including learning and memory. Methods: In the present study, we evaluated the effects of agmatine on cognitive performance and oxidative damage in intracerebroventricular (i.c.v.) streptozotocin (STZ) model of Alzheimer's disease (AD). Adult male Sprague-Dawley rats were injected STZ (3mg/kg, i.c.v, bilaterally) on days 1 and 3. The learning and memory patterns were assessed by using passive avoidance, Morris water maze, and closed field activity tests. Also, malondialdehyde (MDA), glutathione (GSH) levels and myeloperoxidase (MPO) activity have been determined as the parameters of oxidative damage. The behavioral tests were performed after 14 days from the first injection of STZ. Rats with impaired learning and memory performance were treated with intraperitoneal (i.p.) agmatine (40 mg/kg) twice daily for 7 days. After agmatine treatment, rats were subjected to the aforementioned behavioral tests again. Immediately after decapitation of the rats, the brains were collected and analyzed for oxidative damage parameters. Results: Agmatine improved the STZ-induced both spatial and emotinal memory impairment and oxidative damage. Findings of the study demonstrated the effectiveness of agmatine in reversing the cognitive deficits as well as the oxidative damage caused by i.c.v STZ. Conclusion: Taken together, our results have provided experimental evidence suggesting a possible therapeutic potential of agmatine as a regulator in etiopathogenesis of neurodegenerative diseases such as Alzheimer's disease.
Keywords: Farmakoloji ve Eczacılık